PROFIL USAHA NASI KUNING DI KECAMATAN TUMINTING KOTA MANADO (Studi Kasus Nasi Kuning Ci’ Ida) - Rival N. Abidjulu; Theodora M. Katiandagho; Agnes E. Loho (Sam Ratulangi University, 2015)
The aim of this study was to determine the profile of the business yellow rice in District Tuminting, Manado City. The business profile is limited to the amount of profit earned. The study was conducted in Yellow Rice Ci'Ida Tuminting District of Manado City. Data were collected by interview directly with the owners of yellow rice. Variables are calculated for characteristic of entrepreneurs, age, education, long sought, establishment, the owners of capital, organization structure, licensing, production, product type, production process, type of production, packaging and sales, raw materials, labor, buildings and equipment. Yellow rice effort Ci 'Ida is a small business has been operating since 1962 using its own capital and maintain recipes from parents. The yellow rice businesses serve customers every day from 07.00- 11:00 am andÂ 05:00 to 10:00 p.m.. The amount of raw materials used rice ranges between 8-12 kg. On Saturday and Sunday is the highest demand. The highest demand on the benefits obtained is Rp 445 039 per day.